The extraction of essential oil from Quercus infectoria (Manjakani) galls using supercritical carbon dioxide pressure swing technique - Rosland Abel, Stashia Eleaness (2013)
The study of essential oil ofQuercus infectoria (Manjakani) was carried out usingsupercritical carbon dioxide (SC-CO2) extraction. Twotechniques were tested Soxhlet extraction and SC-CO2extractionwith pressure swing technique.The experiments of SC-CO2 extractioninvestigated the effect of pressure and temperature on extraction yields and solubility of galls oil. The extraction were performed at pressuresrange of 35 to 48 MPa, temperaturesbetween 40 and 60ºCwith extraction time of 30 to 60 minutes.The experiments were designed usingResponse Surface Methodology (RSM) to determine the optimum conditions. In this study,SC-CO2 extractioncombined with the pressure swing technique produced higher oil extracted compared to the continuos SC-CO2 extraction with 2.58 % and 1.12 % yield, respectively. The analysis ofRSM indicated that the extraction temperature has a major linear effect on the galls oil extractionwith 17.92 % yield. The optimum extraction process parameters were for pressure of 38 MPa, temperature of 75 °C and extraction time of 54 minutes with 1.12 % yield. The experimentalsolubility data was successfully correlated using Chrastil model with the coefficient of determination (R2) value of 0.95.SC-CO2 extraction combined with the pressure swing techniqueproved of potential to produce greater yield by usingmuch lower SCCO2compared to the continuos SC-CO2 extraction. The identification of bioactive compounds from essential oil was analyzed using aHigh Performance Liquid Chromatography (HPLC) analysis, and it was observed thatQuercus infectoria galls oil contained gallic acid as the major component at the retention time of 2.79 min.